Malay poisons and charm cures - Gimlette, John D. (Orchid Press, 2011)
First published almost a century ago, Malay Poisons and Charm Cures remains a classic and still definitive reference on the pharmacopoeia and practices of Malay healers, shamans (bomoh) and sorcerers (pawing).